Pengaruh Penambahan Daun Salam (Eugenia polyantha) Pada Pembuatan Telur Asin Ayam Niaga Petelur Terhadap Indeks Kuning Telur (IKT), Indeks Putih Telur (IPT) Dan Penurunan Bobot Telur - Sucianty, Hera Siam; Santosa, Singgih Sugeng; Roesdiyanto, Roesdiyanto (ANGON: Journal of Animal Science and Technology, 2019)
The aim of this research was to investigate the effect of the best salam leaves (Eugenia Polyantha) concentration in salted eggs on the yolk index, albumen index, and the weight decrease of egg. One hundred unit eggs of commercial layer chicken, was used in this experiment with the design Complete Randomized Design (CRD), as the treatment namely concentration of salam leaves PO (20% salt), P1 (250 gr + 20% salt), P2 (500 gr + 20% salt), P3 (750 gr + 20% salt) and each treatment was four replicated. Yolk index, albumen index, and the weight decrease of egg was used as variabel measured. The result of variance analysis shown that salam leaves (Eugenia Polyantha) concentration no significant effect (>0,05) on the yolk index, albumen index, and the weight decrease of the egg. The conclusion that salam leaves concentration until 750 gr produced salted egg with yolk index, albumen index, and the weight decrease of egg similar.